Painless project management : - McGhee, Pamela (John Wiley & Sons, 2007)
Project management is a vital and growing component of many organizations and can literally make or break a company. In this step-by-step guide, two project management consultants present a comprehensive guide to effective project management, complete with real stories and case studies from actual project managers. This straightforward guide cuts through the technical jargon to present an easy-to-follow, easy-to-learn approach to executing any project from beginning to end. Project managers, as well as those who want to learn more about project management, will find this guide to be an indispensable resource for all their projects.